2017
DOI: 10.1080/17461391.2017.1324525
|View full text |Cite
|
Sign up to set email alerts
|

The dangerousness of mountain recreation: A quantitative overview of fatal and non‐fatal accidents in France

Abstract: In France, there is a growing enthusiasm for outdoor sports and recreation. In the meantime, the risk of both severe and frequent injury associated with active pursuits in mountain areas is acknowledged. This paper tackles accidents related to mountain sports, with a focus on three critical activities: hiking, mountaineering and ski touring. The aim consists of estimating the actual number of accidents (whether they entailed deaths or injuries) in the three above-mentioned activities. In order to align the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“… 21 The calculated mortality index decreased by about 40% from 2006 to 2014 and the actual value is comparable to data reported from France for hiking on paths (4%) but lower compared with hiking off paths or mountaineering (10%–15%). 26 This development may indicate that mountain hiking became safer during the evaluated period with respect to fatal falls.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 21 The calculated mortality index decreased by about 40% from 2006 to 2014 and the actual value is comparable to data reported from France for hiking on paths (4%) but lower compared with hiking off paths or mountaineering (10%–15%). 26 This development may indicate that mountain hiking became safer during the evaluated period with respect to fatal falls.…”
Section: Discussionmentioning
confidence: 90%
“…Theincrease in non-fatalities (about 50 %) from 2006 to 2014, recorded by the Austrian Alpine Police, could be caused by the increasing popularity of mountain hiking in the Austrian Alps. Although the exact number of mountain hikers and its development remains elusive, 26 there is evidence of a growing popularity during the last two decades. The number of members of the Austrian and the German Alpine Association (OeAV and DAV, respectively) may be considered as a surrogate for the numerical development in mountain sport active individuals in the Austrian Alps.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of overnight stays in Austria increased by approximately 10% from 2014 to 2018 [17], the average death rate (102 deaths per year) during this period was approximately 20% lower compared to the years from 1997 to 2001 and 2002 to 2006 (123 and 119 deaths per year, respectively) [13,15]. For France, Soulé et al reported approximately 25 fatalities per year, calculated for a 4 year period, with a slight predominance of traumatic (approximately 45%) versus non-traumatic accidents (approximately 35%) and nearly 20% disappearances [20]. In Austria, similar distributions of the causes of death have been reported, with sudden cardiac deaths (44%) and the consequences of falls (46%) responsible for approximately 90% of all fatalities in mountain hiking [16,21] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The number of subjects at risk, e.g., all ski tourers, is often unknown for the assessment of the mortality risk and therefore the mortality index (MI; number of fatalities per number of accidents) has been introduced. A recent study from France reported a MI of 8% for ski touring, which was lower than that for mountaineering in rocky or icy terrains (MI: 10%) or climbing a Via Ferrata (MI: 10%) but was higher than for hiking on a trail (MI: 4%) [55]. Long-term mortality recordings from the Austrian Alps do not show any change with time [15,17].…”
Section: (Alpine) Ski Tourersmentioning
confidence: 99%